1991
DOI: 10.1161/01.str.22.5.674
|View full text |Cite
|
Sign up to set email alerts
|

Biphasic striatal dopamine release during transient ischemia and reperfusion in gerbils.

Abstract: To clarify the nature of ischemic striatal dopamine release during the earliest periods of neuronal injury, we used chronoamperometry to measure dopamine levels every 60 seconds during various durations of ischemia in 32 gerbils. Catecholamine-selective electrodes were implanted into the brains of anesthetized gerbils subjected to 2, 5, or 10 minutes of transient forebrain ischemia or permanent forebrain ischemia. Four control animals showed a stable chronoamperometric baseline. In the six gerbils subjected to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
9
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 37 publications
2
9
0
Order By: Relevance
“…Striatal dopamine release has also been demonstrated in response to ischaemia. Ahn et al. (1991) studied the effect of cerebral ischemia on dopamine release in gerbils and found that both early ischaemia and reperfusion resulted in biphasic dopamine release within the striatum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Striatal dopamine release has also been demonstrated in response to ischaemia. Ahn et al. (1991) studied the effect of cerebral ischemia on dopamine release in gerbils and found that both early ischaemia and reperfusion resulted in biphasic dopamine release within the striatum.…”
Section: Discussionmentioning
confidence: 99%
“…Striatal dopamine release has also been demonstrated in response to ischaemia. Ahn et al (1991) studied the effect of cerebral ischemia on dopamine release in gerbils and found that both early ischaemia and reperfusion resulted in biphasic dopamine release within the striatum. It could be postulated that the high volume CED infusions in this study resulted in a period of relative hypoxia within the putamen resulting in dopamine release.…”
Section: Discussionmentioning
confidence: 99%
“…Both excessive entry of calcium into neurons and increased DA release (Ahn et al ., 1991 ;Akiyama et al, 1991 ;Bhardwaj et al, 1990) have been shown to contribute to neuronal damage in ischemia. Some degree of neuroprotection has been achieved with modifiers of both processes (Clemens and Phebus, 1987;Bielenberg and Burkhardt, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…NMDA receptors are normally activated by endogenous glutamate and its coagonist glycine (Gly) (Kleckner and Dingledine, 1988), acting at its own receptor within the NMDA receptor/ channel complex . Extracellular DA levels are elevated in striata of animals that have undergone ischemia (Harik et al ., 1986 ;Brannan et al ., 1987 ;Ahn et al ., 1991 ;Koorn et al ., 1992) . Using in vitro measurements of [3 H]DA release from striatal slices under conditions in which changes in uptake of [ 3 H]DA were excluded, we have previously shown that NMDA-stimulated [3 H]DA release is enhanced in tissue from animals subjected to 10 min of ischemia, and up to 24 h of reperfusion (Werling et al ., 1993) .…”
mentioning
confidence: 99%
“…It is not clear that whether dopamine protect or aggravate the damage after cerebral ischemia and reperfusion [1][2][3][4][5][6] . Therefore, study of the alterations in dopamine may lead to improvements in the treatment of cerebral ischemia.…”
mentioning
confidence: 99%